Pelatihan Pengenalan Kopi dari Bean ke Cup di Sekolah Islam Terpadu Insantama Leuwiliang, Bogor - Hidayati Fatchur Rochmah; Ade Astri Muliasari; Wina Yulianti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Educational activities introducing coffee plants from bean to cup in community service activities had been carried out at the Integrated Islamic School (SIT) Insantama Leuwiliang, Bogor. The method of implementing activities were carried out in two ways, offline for teacher and online for student participants. Material delivery using presentation methods and simulations coffee cup testing. Evaluation of community service activities were carried out by distributing questionnaires. Evaluation of the results of community service activities at SIT Insantama Leuwiliang showed that community service activities were useful and received good responses from teachers and junior high school students. Submission of materials in introduction to coffee plants is important and has been conveyed clearly. The results of the selection materials, needed for further community service activities are materials related to junior high school students in the form of experiments, making tofu and tempe, effective online learning methods, fruit cultivation, plant cultivation in narrow yard (housing), making hand soap, the introduction of Covid 19 and making of meatballs.